2017
DOI: 10.1159/000464096
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy as Adjuvant Treatment for Idiopathic Sudden Sensorineural Hearing Loss after Failure of Systemic Steroids

Abstract: We evaluated the outcomes of and prognostic factors for idiopathic sudden sensorineural hearing loss (ISSNHL) treated with adjuvant hyperbaric oxygen therapy (HBOT). A retrospective review of clinical data was performed for 167 patients with ISSNHL who failed to respond to systemic steroids and were treated by adjuvant HBOT at Shizuoka Saiseikai General Hospital. We analysed the clinical outcomes, the averaged 5-frequency hearing level after systemic steroids, patient age, the interval between post-steroids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…In the present study, the hearing recovery rate was not influenced by the patient age, presence of concomitant systemic diseases (diabetes mellitus and hypertension), or other prognostic factors except for the presence of vertigo, as discussed in our previous study [Hosokawa et al, 2017a]. One limitation of this study is that we measured the hearing thresholds during the time course of treatment and showed the absolute hearing gain value; however, we did not evaluate speech perception, which reflects actual improvements in the quality of life [Pezzoli et al, 2015].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study, the hearing recovery rate was not influenced by the patient age, presence of concomitant systemic diseases (diabetes mellitus and hypertension), or other prognostic factors except for the presence of vertigo, as discussed in our previous study [Hosokawa et al, 2017a]. One limitation of this study is that we measured the hearing thresholds during the time course of treatment and showed the absolute hearing gain value; however, we did not evaluate speech perception, which reflects actual improvements in the quality of life [Pezzoli et al, 2015].…”
Section: Discussionsupporting
confidence: 79%
“…HBOT and SS, hyperbaric oxygen therapy combined with systemic steroid therapy; IT and SS, intratympanic steroids combined with systemic steroid therapy; SS alone, systemic steroid therapy only; CR, complete recovery; GI, good improvement; FI, fair improvement; NC/DR, no change or deterioration. onset of symptoms and treatment initiation, as described in our previous study [Hosokawa et al, 2017a]: ≤7 days and > 7 days. The average times to start therapy in each group are 4.5 days in the HBOT + SS, 4.5 days in the SS alone, and 14.5 days in the IT + SS group, respectively.…”
Section: Effect Of the Treatment Timing On Hearing Improvementmentioning
confidence: 92%
“…Among other subgroups of the statistical model and the time point of response assessment, the benefit of HBOT on complete hearing recovery was similar. For any hearing recovery, the favorable results of the HBOT + MT group compared Odds ratios (OR) with 95% CIs are shown by individual studies describing pooled overall benefits for complete hearing recovery 7,[10][11][12][13][14][15][16][18][19][20][21][22]24 (A) and for any hearing recovery 7,[10][11][12][13][14][15][16][17][18][19][20][21][22]24 with the MT alone group were consistent across all subgroups (eFigure 3 in the Supplement).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…ITS or HBO therapy applied either as salvage or adjuvant therapy for ISSNHL has shown positive results in terms of hearing improvements. [9] But there is still ongoing controversy about which salvage therapy is better. Furthermore, to the best of our knowledge, there is very limited data regarding the efficacy of HBO therapy following combined steroid (systemic+ITS) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10,13,14] The results of salvage HBO therapy in previous studies are demonstrated in Table 4. [9,[14][15][16][17][18] To date, no reports have been published about the hearing outcomes of salvage HBO therapy after combined steroid treatment. The results of this study indicate that there is still something to do after combined steroid treatment in ISSNHL.…”
Section: Discussionmentioning
confidence: 99%